Health Belief, Psychological Conditions, and Treatment-Seeking Behavior in Caregivers of Stunting Toddlers in Rural Areas - Indanah, Indanah; Mauludina, Ibtasama; Jauhar, Muhamad (Journal of Bionursing, 2025)
Stunting in toddlers is still a global problem that has a serious impact on the social and economic aspects of society. The increase in the number of stunting cases that are not treated causes the condition of toddlers to worsen. This is caused by the health beliefs and psychological condition of the caregiver. This research aims to analyze the relationship between health beliefs psychological conditions and treatment-seeking behavior. This research design uses correlational analytics with a cross-sectional approach. The independent variables are health beliefs and psychological conditions, while the dependent variable is treatment-seeking behavior. This research was conducted in the Keling II Community Health Center Working Area, Jepara Regency in January 2025. A sample of 100 caregivers of stunted toddlers was taken using a purposive sampling technique according to certain criteria. The research instruments used the Brief Illness Perception Questionnaire (BIPQ-8), Perceived Stress Scale (PSS-10), and General Help-Seeking Questionnaire (GHSQ). Data analysis used the chi-square test. The research results show that there is a significant relationship between health beliefs and treatment-seeking behavior in caregivers of stunting toddlers with a value of p = 0.000 (p < 0.05) and a correlation coefficient value (r = 0.417), and there is a significant relationship between psychological conditions and treatment seeking behavior with a value of p < 0.001 (p < 0.05) with a moderate correlation coefficient (r = 0.420). Health beliefs and psychological conditions of care givers shape treatment-seeking behavior. There is a need for intervention to improve treatment-seeking behavior by increasing health beliefs and the psychological condition of caregivers.